Legal Issues for Technology-Based Loans in Indonesia - Dimas Pramodya Dwipayana; I Gusti Ayu Ketut Rachmi Handayani; Siska Diana Sari; Dimas Firmansyah Wijaya (Universitas Muhammadiyah Tangerang, 2020)
Technological developments in the era of globalization have crept into the financial world. The high demand for people in financial matters makes financial technology grow rapidly. Community problems in meeting financing needs are increasingly needed so funding sources are needed. In practice, there are insufficient funding sources to help the community, the process is complicated and requires a long time to make peer to peer lending begin to be looked at by Indonesians who are looking for sources of funding. Legal norms in positive law and by type of library research. The conclusion of this research is that users must protect more in carrying out all activities that require financial technology, borrowing money, and in conducting peer to peer lending practices in order to guarantee legal certainty in accordance with the laws and regulations in force in Indonesia